Karakteristik Sosial Ekonomi Masyarakat Pesisir : Studi Kasus Kelurahan Leato Utara - miraz, nurhawaliya; Azzahra Sudirman, Azisah; Putalan , Reinal (Program Vokasi UNG, 2024)
This study aims to analyze the socio-economic characteristics of coastal communities in Leato Utara Subdistrict, Gorontalo City, by highlighting social structure, economic stratification, gender construction, cultural evolution, and income adaptation strategies. Using a qualitative approach with a field case study design, data were collected through participatory observation, in-depth interviews, and documentation, then analyzed interactively. The results show that the community mainly depends on fishing activities with a profit-sharing system that creates a social hierarchy between labor fishermen and boat owners. Solidarity and informal institutions persist even though modernization gradually shifts traditional practices. Women significantly contribute through micro-businesses and fish processing, indicating a shift in gender roles. Income diversification through aquaculture, small-scale farming, and local tourism is identified as an adaptive response to economic fluctuations. These findings enrich the literature on Indonesian coastal sociology by emphasizing the importance of strengthening local institutions, preserving local wisdom, and empowering gender roles as pillars of sustainable coastal development. The uniqueness of this study lies in mapping the relationship between cultural evolution and economic adaptation in traditional coastal communities, which is rarely revealed in similar studies. Keywords: cultural evolution, gender construction, coastal community, socio-economic structure, adaptation strategy.